A mezőgazdaság térségi folyamatai. A termelőerők térbeli megoszlása a hetvenes évek elején - Enyedi, Györgyné (Tér és Társadalom, 1988)
In her present paper the author reviews spatial processes in agriculture during some one and half decade (1971-1984). She focusses the attention on the spatial mobility of productive forces, the regional variations in personal incomes and in enterprise profits, their relationships, and finally, the changing spatial structure of production. The author has established that the regional proportions of land, labour, assets and income have deteriorated, the spatial incongruence between the various factors of production has increased and thereby the possiblities of a rational use of resources have diminished. The lasting and deepening differentiation of enterprise income started a rapid degradation process in certain regions. In this process of differentiation those regions got in a privileged position where the economic and the infrastructural background was developed instead of those with favourable natural endowments. The spatial pattern of personal incomes and investments was not only dissimilar but contrasting to that of enterprise incomes: it demonstrated a clear tendency towards levelling up. The structure of production - which had demonstrated little regional specialization earlier - continued to be more and more alike over space. Agrarian policy has played an important role in this process of spatial assimilation of production structure though it has all the time attempted to curb the process of differentiation born by this policy itself as well as to curb the process of spatial assimilation of the production structure. Finally, the author presents suggestions for the elaboration of a new agrarian policy which would better conform to new circumstances.